2023
DOI: 10.1039/d3py00096f
|View full text |Cite
|
Sign up to set email alerts
|

Carbamate thermal decarboxylation for the design of non-isocyanate polyurethane foams

Abstract: Polyurethane foams remain at the forefront of cushioning, insulation, packaging, and structural applications. Risk of exposure to isocyanate-containing precursors during foaming operations directly contributes to the regulation of isocyanates, thus...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…9−11 In contrast, rigid PUs employ higher concentrations of hydrogen-bond-containing hard segments, which lead to higher T g s and moduli. 12,13 This feature of modular design empowers PUs to impact a wide range of technologies, including coatings, 14,15 adhesives, 16,17 biomedical materials, 18−20 automotive parts, 21−23 foams, 24,25 electronics, 26 and more. 27 Traditionally, the processing of thermoplastic polyurethanes (TPUs) employs injection molding, extrusion, blow molding, and compression molding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9−11 In contrast, rigid PUs employ higher concentrations of hydrogen-bond-containing hard segments, which lead to higher T g s and moduli. 12,13 This feature of modular design empowers PUs to impact a wide range of technologies, including coatings, 14,15 adhesives, 16,17 biomedical materials, 18−20 automotive parts, 21−23 foams, 24,25 electronics, 26 and more. 27 Traditionally, the processing of thermoplastic polyurethanes (TPUs) employs injection molding, extrusion, blow molding, and compression molding.…”
Section: Introductionmentioning
confidence: 99%
“…Polyurethanes (PUs) offer superior versatility compared to conventional VP resins due to modular molecular design strategies that effectively tailor thermomechanical properties for specific applications. PUs represent a subgroup of elastomeric materials that rely on soft segments with a low glass transition temperature ( T g ) to provide flexibility and hard segments with intermolecular hydrogen bonding that impart physical cross-linking and provide desirable mechanical performance. In contrast, rigid PUs employ higher concentrations of hydrogen-bond-containing hard segments, which lead to higher T g s and moduli. , This feature of modular design empowers PUs to impact a wide range of technologies, including coatings, , adhesives, , biomedical materials, automotive parts, foams, , electronics, and more …”
Section: Introductionmentioning
confidence: 99%
“…This synthesis readily produces both linear and crosslinked architectures and exhibits in situ CO 2 formation for producing NIPU foams. [31,32] The phase separation behavior of BCI-derived NIPU segmented copolymers has not been thoroughly investigated or reported. This manuscript demonstrates phase separation within polyether urethanes synthesized in the absence of isocyanates.…”
Section: Introductionmentioning
confidence: 99%
“…Monie et al reported a self-blown NIPU foams based on decarboxylation of cyclic carbonates by thiols or latent thiol via S-alkylation at 80–100 °C. , Bourguignon et al reported self-blown NIPU foams by water-induced decarboxylation of cyclic carbonate at 80–100 °C . Recently, Sintas et al reported a CO 2 -blown NIPU foam through thermal decarboxylation of bis-carbonylimidazolide monomers at 160 °C . The current foaming processes for NIPU require flammable and noxious chemicals, nonsustainable blowing agents, or high temperatures.…”
mentioning
confidence: 99%
“…Physical blowing agents such as Solkane 14−17 (hydrofluorocarbon) and supercritical CO 2 , 18 chemical blowing agents such as CO 2 generated from maleic acid/citric acid 19,20 and NaHCO 3 21 were also studied for preparing NIPU foams. Self-blown NIPU foams were reported based on the in situ carbon dioxide generation from partial decarboxylation of sorbitol-derived bis(cyclic carbonate)s 22 or resorcinol-based bis(cyclic carbonate)s 23 27 The current foaming processes for NIPU require flammable and noxious chemicals, nonsustainable blowing agents, or high temperatures. Therefore, the development of a sustainable foaming method for NIPU at lower temperatures is of great interest.…”
mentioning
confidence: 99%